β-Cyclodextrin-Based Nanosponges Inclusion Compounds Associated with Gold Nanorods for Potential NIR-II Drug Delivery - Sebastián Salazar Sandoval; Elizabeth Cortés-Adasme; Eduardo Gallardo-Toledo; Ingrid Araya; Freddy Celis; Nicolás Yutronic; Paul Jara; Marcelo J. Kogan (MDPI AG, 2022)
This article describes the synthesis and characterization of two nanocarriers consisting of β-cyclodextrin-based nanosponges (NSs) inclusion compounds (ICs) and gold nanorods (AuNRs) for potential near-infrared II (NIR-II) drug-delivery systems. These nanosystems sought to improve the stability of two drugs, namely melphalan (MPH) and curcumin (CUR), and to trigger their photothermal release after a laser irradiation stimulus (1064 nm). The inclusion of MPH and CUR inside each NS was confirmed by field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, Fourier transform infrared spectroscopy, (FT-IR) differential scanning calorimetry (DSC), transmission electron microscopy (TEM), and proton nuclear magnetic resonance (1H-NMR). Furthermore, the association of AuNRs with both ICs was confirmed by FE-SEM, energy-dispersive spectroscopy (EDS), TEM, dynamic light scattering (DLS), ζ-potential, and UV-Vis. Moreover, the irradiation assays demonstrated the feasibility of the controlled-photothermal drug release of both MPH and CUR in the second biological window (1000-1300 nm). Finally, MTS assays depicted that the inclusion of MPH and CUR inside the cavities of NSs reduces the effects on mitochondrial activity, as compared to that observed in the free drugs. Overall, these results suggest the use of NSs associated with AuNRs as a potential technology of controlled drug delivery in tumor therapy, since they are efficient and non-toxic materials.